Augmentation gluteoplasty with intramuscular implants to improve the physical measurement - Alicia Maria Tamayo Carbón; Diana Katherine Cuastumal Figueroa; Carlos Alberto Gaitán García; Olga Rodríguez Sánchez (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Gluteal region has been considered one of the most observed areas either in women as in men and constitutes a representative icon of corporal beauty. In the last years the desire of women to increase this anatomical region with implants has been increased. Objective: To determine the aesthetic results of the augmentation gluteoplasty with intramuscular implants. Methods: A prospective, longitudinal and descriptive study of 25 women that went to the Plastic Surgery Service outpatient consultation of Hermanos Ameijeiras Clinical Surgical Hospital was carried out from August, 2016 to February, 2019, to request the increase of the gluteal region with implants. Results: In the series there was a prevalence of the 31 to 40 age group (36.0%) and the skin phototype III (88.0%); also only 6 patients presented complications (24.0%), among which seroma (20.8%), asymmetry (12.5%) and anastomotic dehiscence (8.3%) were notable. A significant increase of the gluteal projection after the intervention was observed (α =0.05) and the results were good in most of the members of the sample (84.0%). Conclusions: The augmentation gluteoplasty with intramuscular implants is a safe procedure and offers favorable aesthetic results.